Single-cell transcriptomic analysis of the human vascular atlas provides new insights into vasorelaxation redundancy and heterogeneity - Avolio, Elisa; Pearce, Sarah F.; Wambeke, David; Madeddu, Paolo (Frontiers in Cardiovascular Medicine, 2025)
BackgroundEndothelial cells (ECs) induce vascular smooth muscle cells (VSMCs) relaxation via nitric oxide (NO), prostacyclin (PGI₂) and hyperpolarizing factors. Recent whole-genomic, single-cell transcriptomic analysis of human vascular cells has revealed angiotypic heterogeneity. However, it remains unknown whether vasorelaxant mediators reiterate this pattern.Working hypothesisThe expression of “sentinel” gene transcripts provides a first insight into angiotypic and organotypic heterogeneity of vasorelaxation.MethodsThe expression of NO- and PGI2-generating enzymes and potassium channels was evaluated by analyzing single-cell RNA-sequencing data derived from the Human Vascular Cell Atlas. The data were transformed into a Seurat object (ShinyCell) and processed using the RStudio software. The results were visualized through uniform manifold approximation (UMAP) and projection representations of single-cell profiles.ResultsNO synthase (NOS3) expression differed across EC subpopulations, with the highest enrichment in spleen littoral ECs, followed by venous, arterial, and capillary ECs. PGI2 synthase (PTGIS) demonstrated the highest frequency in arterial and venous ECs and VSMCs. At the same time, it was low in capillary, littoral, and lymphatic ECs and pericytes. The PGI2 receptor gene (PTGIR) was expressed in vascular mural cells. A marked angiotypic heterogeneity was noted regarding potassium channels. Overall, the gene transcripts mentioned above were rarely co-expressed. Comparing two cohorts aged 20 to 49 and 50 to 80 revealed NOS3 expression was less frequent in venous and littoral ECs of older individuals. In contrast, arterial and capillary ECs were modestly affected by age. PTGIS frequency was elevated with aging in VSMCs and, to a lesser extent, in venous and arterial ECs. The KCNMA1 gene, which encodes the big potassium channel alpha subunit 1, was almost doubled in the VSMCs from the older group. Finally, organotypic differences were identified in vascular cells derived from the coronary arteries, brain, and uterus.ConclusionThis initial report indicates a striking heterogeneity in the expression of genes encoding vasorelaxant pathways in human vascular cells, with age exerting angiotypic influences. Reiteration on a larger number of cells and genes, as well as validation of data using post-transcriptional methods, is warranted to firmly confirm the hypothesis about redundant heterogeneity of vasorelaxant mechanisms.